Determination and uniformity: the problem with speech-act theories of fiction - Predelli, Stefano (Springer, 2017)
Taking inspiration from Searle’s ‘The Logic of Fictional Discourse’, this essay presents an argument against different versions of the so-called ‘speech act theory of fiction’. In particular, it argues that a Uniformity Argument may be constructed, which is additional to the Determination Argument commonly attributed to Searle, and which does not rely on his presumably controversial Determination Principle. This Uniformity Argument is equally powerful against the ‘Dedicated Speech Act’ theories that Searle originally targeted, and the more recent, Grice-inspired versions of speech-act approaches to fictional discourse.